La Danza Como Medio De Construcción De Identidad En La Ciudad De Armenia (2014)
In this research, a study population of the city of Armenia, whose aim was to uncover what is built using dance as identity in the city was made. Likewise, the project was based on the approach of complementarity of Murcia and Jaramillo, and the social imaginary as a theory of support, using in the first instance the field diaries as a technique for data collection in a second time we used the depth interviews to the relevant individuals in the work unit, and after that an analysis of the collected data was performed. The subjects in the sample were fourteen members representing different groups in the city dance performances, including dance practitioners with more than two years of experience, less than two, and teacher who has been in the dance but now is found away from their practice. The design consisted of three stages, the first approach to reality ; which a scheme of social intelligibility, the second, the definition of the collection plan and deepening each of the categories of the scheme, on the axis of the same actors and finally the construction of meaning is defined, mediated by triangulating information . Among the findings highlighted the fact that the dance is seen as a factor of social empowerment, which in the framework of the theory, let visibilizarla as a stage of recognition of others and yourself in the construction of identity in the town of Armenia .